Using the AquaCrop model to assess the cotton yield response to three irrigation schedules in the Río Dulce Irrigation System, Santiago del Estero, Argentina = Uso del modelo AquaCrop para evaluar la respuesta del rendimiento del algodón a tres programaciones de riego en el Sistema de Riego del Río Dulce, Santiago del Estero, Argentina = Uso do modelo AquaCrop para avaliar a resposta da produtividade do algodão a três programas de irrigação no Sistema de Irrigação Rio Dulce, Santiago del Estero, Argentina - Angella, Gabriel Augusto; Prieto Angueira, Salvador; Fereres Castiel, Elías; García Vila, Margarita; Prieto Garra, Daniel (INIA Uruguay y Facultad de Agronomía, Universidad de la República, 2024)
This work evaluates the cotton response to irrigation scheduling using AquaCrop, in the Río Dulce Irrigation System (SRRD), Santiago del Estero, Argentina. The model was calibrated and validated to simulate the cotton´s growth and yield for the SRRD, where most of the cotton is grown in a cropping system called narrow rows (0.52 to 0.76 meter between rows, 200,000 to 220,000 plants per hectare). The model adaptation to different cultivars and agronomical practices was noteworthy. Then, the impact of three different irrigation schedules on cotton production was assessed using a series of 35 years of daily climatic data. The irrigation scenarios were defined based on the farmers’ practices and on the rotational water delivery of the SRRD. The highest yields were attained when irrigation was applied at 25 and 55 days after sowing (DAS), followed by 55 DAS, and, finally, 55 and 85 DAS. Considering both the yields and the water use, irrigating at 25 and 55 DAS would be the best option for a normal season in the SRRD. This work shows the usefulness of combining the use of crop simulation models, field measurements and long-term weather data to analyze yield trends and irrigation water use under different scenarios.